Interest rates and the additional costs of the informal sector (2020)
In the rural areas of Colombia, farmers seek funding for their production activities. Credit markets are segmented between formal and informal sectors. Formal credits offer better debt conditions than informal credits such as lower interest rates, bigger loans, and longer repayment terms. At the same time, informal credits have additional costs such as threats, violence, or reputational damage. Informal credits are still widely used because some credit is better than none for farmers with low capital endowments. I find that formal interest rates are 0.8% per month while informal interest rates are 14.9% per month between 2010, 2013, and 2016 using the ELCA Survey. I estimate the additional costs of using credit from the informal sector using a model of rural credit and find that, on average, acquiring credit from this sector increases interest rates in 65.4 percentage points per month in addition to the repayment of debts.